The Paradox of Inclusion: Non-Binary Equity, Diversity, and Inclusion Work in a Dualistic World - Patrick Goh; Lucy Aphramor; Candis Mary-Dauphin (Murmurations)
Despite decades of policy and programming, Equity, Diversity, and Inclusion (EDI) initiatives remain constrained by the binary logic embedded in traditional organisational thinking. This paper critiques the positivist and dualistic assumptions that shape the environments in which EDI practitioners operate. We argue that modernist frameworks oversimplify complex social realities, obscure systemic harm and trauma, and reinforce hierarchical structures rooted in coloniality and white supremacy.